PERANAN TOKOH SOCIAL ENTREPRENEUR DALAM PEMBERDAYAAN MASYARAKAT PERSPEKTIF MAQASID ASY-SYARI’AH - Muharrom, M. Syahrul; Hidayat , Moh. Nurul; Muhtadi, Ridan (Ulumuna: Jurnal Studi Keilsman, 2024)
This study aims to analyze the role of a social entrepreneur in community empowerment from the perspective of maqasid al-shari’ah, using a case study of Haji Her (H. Hoirul Umam), CEO of Bawang Mas Group in Pamekasan Regency. Haji Her is recognized as a social change agent who consistently advocates for the welfare of tobacco farmers in Madura through a social entrepreneurship model. This research employs a qualitative approach using data collection techniques such as in-depth interviews, documentation, literature review, and online sources. The findings reveal that Haji Her’s social entrepreneurship is reflected in various aspects of the Business Model Canvas, including a social value proposition through purchasing farmers’ tobacco at high prices, providing education and training to farmers, and establishing the Paguyuban Pelopor Petani dan Pedagang Tembakau Se-Madura (P4TM). His business activities are not solely profit-oriented but are also focused on social sustainability and empowerment grounded in Islamic values. From the perspective of maqasid al-shari’ah, Haji Her’s contributions align with the five core objectives: preservation of religion, life, intellect, wealth, and progeny. These contributions are manifested through CSR programs, the development of social infrastructure, involvement of religious scholars in decision-making, and character education rooted in Islamic boarding schools (pesantren). This study concludes that Haji Her’s maqasid al-shari’ah based social entrepreneurship model can serve as a strategic inspiration for the development of holistic and sustainable community empowerment practices. Keywords: social entrepreneurship, community empowerment, maqasid al-shari’ah, Haji Her, Madura tobacco, Business Model Canvas.